Effect of Carvacrol in Attenuating the TNF-α Induced Sarcopenia - Albarrati, Ali Mufraih; Nazer, Rakan Ibrahim (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Sarcopenia is a condition characterized by muscle loss, which is accompanied by inflammation, oxidative stress, and mitochondrial dysfunction. The current treatment of sarcopenia is insufficient in handling the issues it faces, which may need alternative therapy, especially from natural sources. Carvacrol is a natural compound that has shown antioxidant and anti-inflammatory properties previously, making it an ideal choice for evaluating its potential in sarcopenia treatment. Objectives: The objective of this study is to evaluate the effect of Carvacrol in attenuating the TNF-α induced sarcopenia using an in vitro model. Materials and Methods: TNF-α pretreated rat myoblast cells L6 were treated with different concentrations (0.75-12.5 μg/ mL) of carvacrol to determine the cytoprotective effect. Later, TNF-α pretreated L6 cells were treated with the IC50 concentration of carvacrol, and the level of Lactate Dehydrogenase (LDH) leakage, antioxidant enzyme activities (catalase and SOD), ATPase activities (Na⁺/K⁺, Ca²⁺, Mg²⁺), Mitochondrial Membrane Potential (MMP), and gene expression of SIRT1 and AMPK using real-time PCR were evaluated. Results: The IC50 of carvacrol in L6 cells was obtained as 60.87 μg/ mL. The study demonstrated that Carvacrol was able to protect against TNF-α-induced cell toxicity at a dose of 6.25 μg/mL, reducing cell rounding and blebbing. The TNF-α induced LDH leakage was 300 units, which was reduced by carvacrol to 100±11.25 units. The antioxidant enzymes, such as catalase and SOD, were significantly restored to normal levels by carvacrol. In addition, the ATPase levels were also reduced to 3±0.01 mg/dL for Na⁺/K⁺, 2.5±0.01 mg/dL for Ca2+, and 3.5±0.02 mg/dL for Mg²⁺. Carvacrol reduced the mitochondrial depolarization in the treated cells from 31.65±4.25% to 19.0±2.6% significantly. It also upregulated the gene expression levels of SIRT1 (1.6-fold) and AMPK (2-fold) compared to TNF-α-induced downregulation. Conclusion: The results demonstrate that carvacrol has the potential to treat the sarcopenia condition. It has recovered sarcopenia-related muscle toxicity by influencing the antioxidant system, mitochondrial function, and upregulation of SIRT1 and AMPK genes. These findings suggest carvacrol’s potential as a therapeutic agent for sarcopenia, warranting further preclinical and clinical studies.
Keywords: Sarcopenia; Carvacrol; Oxidative Stress; Mitochondria; TNF-alpha.